Clay minerals in sediments of the Arctic Seas. - Kalinenko, Valery V (PANGAEA, 2001)
Distribution of clay minerals in recent sediments on the Arctic shelf off the Eurasian and North American continents is considered. Prominence is given to the East Siberian and Laptev seas. An illite belt established on the base of clay mineral composition in seven Arctic seas spreads from the Beaufort Sea to the White Sea and reveals a mineralogical zonality. The belt can be devided into smectite and chlorite provinces. Factors governing formation of the Arctic illite belt and features of distribution of individual clay minerals are discussed. Identification of the illite belt in sediments on the Arctic shelf complements the system of planetary latitudinal zones of clay minerals formulated by previous researchers.
(Table 2) Relative contents of clay minerals in <0.001 mm grain size fraction from surface layer bottom sediments of the East Siberian and Laptev Seas
Keywords: Archive of Ocean Data; ARCOD; Area/locality; BC; Box corer; Buor Khaya Bay, Laptev Sea; Chaun Bay East Siberian Sea; Chlorite; Chlorite+Kaolinite; Clay minerals; DEPTH, sediment/rock; Dm. Laptev Srait; East Siberian Sea; ESS281; ESS282; ESS284; ESS285; ESS286; ESS288; ESS289; ESS290; ESS291; ESS292; ESS293; ESS295; ESS314; ESS315; ESS316; ESS317; ESS318; ESS320; ESS323; ESS327; ESS328; ESS329; ESS333; ESS334; Illite; Kaolinite; Laptev Sea; Long Strait; QUEEN_Exped; Smectite; X-ray diffraction (XRD)